2010
DOI: 10.1210/jc.2009-2282
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Various Functional and Anatomic Imaging Modalities for Detection of Ectopic Adrenocorticotropin-Secreting Tumors

Abstract: High sensitivity and PPV suggest thoracic CT/MRI plus LOCT scans for initial imaging, with lesion confirmation by two modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
108
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(117 citation statements)
references
References 21 publications
6
108
0
3
Order By: Relevance
“…It has been reported that FDG-PET for detection of the ectopic ACTH source has a sensitivity of 64% and positive predictive values of 53 % [2]. In this case, FDG-PET showed no significant uptake by the S7 tumor which was later identified as bronchial carcinoid tumor, but mild uptake by the S5 tumor which was found to be a cryptococcal granuloma.…”
Section: Reverse Transcription-polymerase Chain Reaction Detection (Rmentioning
confidence: 64%
See 1 more Smart Citation
“…It has been reported that FDG-PET for detection of the ectopic ACTH source has a sensitivity of 64% and positive predictive values of 53 % [2]. In this case, FDG-PET showed no significant uptake by the S7 tumor which was later identified as bronchial carcinoid tumor, but mild uptake by the S5 tumor which was found to be a cryptococcal granuloma.…”
Section: Reverse Transcription-polymerase Chain Reaction Detection (Rmentioning
confidence: 64%
“…It has been reported that SRS for detection of the ectopic ACTH source have sensitivity of 57 % and positive predictive values of 79 % [2]. SRS using 111 In-pentetreotide is a useful tool to detect neuroendocrine tumors with abundant expression of SSTRs [13], among which octreotide binds with higher affinity to SSTR-2 and SSTR-5.…”
Section: Reverse Transcription-polymerase Chain Reaction Detection (Rmentioning
confidence: 99%
“…Reviewafter the administration of corticotrophin-releasing hormone (CRH) has become an established and widely used diagnostic procedure in patients with ACTH-dependent Cushing's syndrome, especially in those cases with a negative or equivocal pituitary MRI finding (89,90,91,92,93) (Fig. 5).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Only a few case reports exist in which ACTH-secreting bronchial NETs could be localised using pulmonary arterial sampling (94,95). However, generally CT, MRI and the different scintigraphy and PET techniques, as mentioned above, are more successful in the localisation of (occult) ACTH-producing extra-pituitary tumours (89,90,91,92,93). …”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Functional imaging studies such as PET and somatostatin receptor scintigraphy (SRS) are complementary imaging tools [68][69][70]. Somatostatin receptor scintigraphy might be considered superior to PET in detecting bronchial carcinoids, especially that these tumors specifically are known to have low proliferation index [69,70]. …”
mentioning
confidence: 99%